(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
In this article, opinions and reflections on the social, psychologii v a pedagogical characteristic of families with children with intellectual disabilities are discussed. Families with children who have intellectual disabilities navigate a unique and complex set of challenges that influence their social, psychological, and pedagogical dynamics. Understanding these characteristics is crucial for educators, therapists, and support networks who aim to provide effective support to these families. The social dynamics of families with children with intellectual disabilities are often shaped by the broader societal attitudes toward disability.